Well-Being in Islamic Income Utilisation: A Longitudinal Qualitative study on Muslim Family - Indah Dewi Nirwana; Agus Suman; Iswan Noor; Atu Bagus Wiguna (AIBPM Publisher, 2022)
This study aims to describe income utilization at the household level from an Islamic perspective. A qualitative approach with semi-structured interviews was carried out on 3 Muslim families longitudinally in 2015 and 2022. In the framework of household income management, Muslim families conduct the planning, implementation, and monitoring processes to spend income meeting their needs. During the planning stage, Muslim families prepare the planning process based on lillahi taala's (everything for god) intentions. Then at the implementation stage, Muslim families carry out activities to fulfill their needs in a halal and Thayib way. As for the monitoring stage, Muslim families spend some of their income through zakat, infaq, and sadaqah as a sustainability act toward the afterlife. Adaptation in income utilization practices can result from several factors: 1) socio-economic status and 2) technological change. Keywords: income utilization, household needs, Muslim family